Assessing Outdoor Thermal Comfort Indicators and Their Influence on Pedestrian Behaviour in Indian Urban Streets: A Systematic Review - Khante, Vandana; Haque, Mazharul (International Journal of Aquatic Research and Environmental Studies, 2026)
The accelerating pace of urban expansion across Indian cities has placed mounting pressure on the built environment, leading to a contraction of outdoor public spaces and a measurable decline in microclimatic quality. As urban streets function as primary sites of pedestrian activity and public life, developing a robust understanding of outdoor thermal comfort has become indispensable to sustainable urban planning and design. The importance of this question is amplified in the Indian context by the country's remarkable climatic diversity, which encompasses extreme summer heat in northern and western plains, humid tropical conditions along the southern coasts, and severe winter cold in the Himalayan belt. This study presents a critical review of research conducted over the last decade on outdoor thermal comfort and its influence on pedestrian behaviour in urban areas. Relevant studies were systematically selected from major academic databases through a rigorous screening and filtering process, covering both developed and developing countries. The review focuses on four key dimensions influencing outdoor thermal comfort: physical, physiological, psychological, and behavioural factors. A comprehensive assessment of indicators and sub-indicators used across the selected studies was undertaken, followed by the identification and consolidation of overlapping parameters to establish a refined set of indicators.The findings reveal that, alongside physical, physiological, and psychological considerations, behavioural factors have received increasing attention in both developed and developing countries due to their significant role in shaping pedestrian responses to outdoor thermal environments. The study highlights the most frequently adopted and prioritized indicators for assessing thermal comfort and pedestrian behaviour. These findings provide a valuable framework for future urban street studies and can support planners, designers, and policymakers in developing thermally comfortable and pedestrian-friendly urban environments.
Keywords: Outdoor thermal comfort; Pedestrian behaviour; Urban heat stress; Thermal comfort indicators; Behavioural adaptation; Urban morphology; Indian cities; Climate-responsive urban design.